Water and land stress in Bolivia, Colombia, Ecuador, and Peru under coupled climate-socioeconomic scenarios - Kuishuang Feng; Xiangjie Chen (Inter-American Development Bank (IDB), 2023)
How to keep water and land stress within planetary boundaries is a major challenge for sustainable development in Latin American countries. Using an environmentally extended global multi-regional input-output analysis (GMRIO) approach, this study simulates future land and water demand for Bolivia, Colombia, Ecuador, and Peru under three climate-socioeconomic scenarios: SSP1-RCP2.6, SSP2-RCP4.5, and SSP5-RCP8.5. Under all three scenarios, land and water demands in all four countries are projected to increase rapidly in the next few decades. By 2050, the demand for cropland in Peru and Bolivia will exceed those countries' planetary boundaries, with the rise in income being the most significant contributor to the rising demand. In addition, foreign demand will significantly drive the growth of water and land demand in Ecuador and land demand in Colombia. Nonagricultural sectors, most notably the mining sector, will be primarily responsible for the increased water demand in Ecuador and Peru, exacerbating competition between those sectors and the agricultural sector for water. In Peru and Bolivia, there is a significant spatial mismatch of water and land resources at the basin level. With hydraulic infrastructure as a prerequisite, developing irrigated agriculture may lead to a water-land trade-off that can significantly alleviate the land stress in those countries.
Keywords: C67; Q01; Q15; Q24; Q25; Q56; 330; Water sanitation; water use; agriculture and food security; climate change; productive transformation; Andean countries